Osteonecrosis of bilateral femoral head in a post COVID-19 patient: case report - Chacko, Ankith; Babu, Murukan; Thomas, Dibin K. (International Journal of Research in Orthopaedics, 2021)
Osteonecrosis of the femoral head, can be secondary to various causes, which can be traumatic or atraumatic. The corticosteroid used is a common cause of non-traumatic osteonecrosis. Various viral infections have been documented to cause osteonecrosis, none of the studies report COVID-19. 23-year-old gentleman diagnosed with COVID-19. He received steroid injections as a part of treatment. Nearly after two months, he was diagnosed to have stage II osteonecrosis of both femoral heads. The cumulative dose of steroid given to the patient was not enough to consider diagnosis of steroid associated osteonecrosis of femoral heads. The combination hypercoagulability, inflammation of blood vessels, and leukocyte/platelet aggregation associated with COVID-19 might have contributed to the development of osteonecrosis in this case. So, it is also important to consider osteonecrosis as an important differential if a patient with past history of COVID-19 come with hip pain.